Proyecto de vida en jóvenes escolarizados de la ciudad de Latacunga. - Calvopiña Panchi, Jessica Elizabeth (2019)
The purpose of this research was to identify how the young people of the last year of the baccalaureate at Primero de Abril Educational Unit, during the 2018-2019 school year, assign meanings to their life project, when facing the completion of their secondary education. To start with the research there was the need to collect and review information to understand this problem of the construction of the life project and address it from the communicational field (meanings assigned to the life project), taking into account that communication is a dynamic process in humans. In addition, approaching it from the field of narrative semiotics, it is said that all discourse is a text, the same one that made it possible to demonstrate the meanings that young people in the last year of the baccalaureate at "Primero de Abril" educational unit assign to their life project. The methodology used in this project was qualitative, since it allowed collecting information from a specific context (secondary youth), in addition a focus group was held in which 2 students participated in parallel, the question guide was previously structured by the researchers. Other techniques that were applied were interviews with experts (vocational counselor and director of the Education District), which were important in this project, because it helped to balance information. Finally, it was found that the students who are in the last year of high school assign a meaning to the continuation of their studies in the university, as an exit to a situation of poverty and unemployment that exists in the country, rather than as a realization of personal order. In addition, they allude to the fact that the construction of their future is only possible with the support of their family, especially in the economic aspect. It concludes that entrepreneurship is not part of the life project, as an option for personal fulfillment, which places them as dependent on their parents and with the sole function of being students. The contribution of this research is for society, because, the construction of a life project in young people who are studying the last year of high school must be worked together (students, teachers and parents) so that strategies are implemented that help to guide young people in their life project, in such a way that they achieve their personal and professional goals.